2021
DOI: 10.1371/journal.ppat.1009992
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies reveal the role of polymorphisms affecting factor H binding protein expression in host invasion by Neisseria meningitidis

Abstract: Many invasive bacterial diseases are caused by organisms that are ordinarily harmless components of the human microbiome. Effective interventions against these microbes require an understanding of the processes whereby symbiotic or commensal relationships transition into pathology. Here, we describe bacterial genome-wide association studies (GWAS) of Neisseria meningitidis, a common commensal of the human respiratory tract that is nevertheless a leading cause of meningitis and sepsis. An initial GWAS discovere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 94 publications
2
25
0
Order By: Relevance
“…The present study compares E. coli whole genomes in colonization and in infection, as done before for Klebsellia pneumoniae (52), S. pneumoniae (55), Staphylococcus aureus (53, 56), Neisseria meningitidi s (57). These GWAS studies presented a range of results, from low heritability (2.6% for S. aureus carriage vs. BSI (53)), to intermediate (36.5% for N. meningitidis carriage vs. invasive meningococcal disease), and an analogously large heritability of 70% for S. pneumoniae invasive disease vs. carriage, along with a handful of significant SNPs (55).…”
Section: Discussionmentioning
confidence: 99%
“…The present study compares E. coli whole genomes in colonization and in infection, as done before for Klebsellia pneumoniae (52), S. pneumoniae (55), Staphylococcus aureus (53, 56), Neisseria meningitidi s (57). These GWAS studies presented a range of results, from low heritability (2.6% for S. aureus carriage vs. BSI (53)), to intermediate (36.5% for N. meningitidis carriage vs. invasive meningococcal disease), and an analogously large heritability of 70% for S. pneumoniae invasive disease vs. carriage, along with a handful of significant SNPs (55).…”
Section: Discussionmentioning
confidence: 99%
“…The preexisting TISS is most closely related to genes of the frp operon, which encodes the distantly related RTX family protein, FrpC, and is intact in N. meningitidis but not in N. gonorrhoeae or commensal Neisseria speices 54,55 . Though the specific function of FrpC is unclear, it is thought to act as an additional adhesin that is dispensable for virulence in a mouse model [56][57][58][59][60] . This important genetic reconstitution event provides a novel example of gene co-option as a major contributing factor in the evolution of bacterial virulence in a commensal genus.…”
Section: Discussionmentioning
confidence: 99%
“…panfeed was also tested for its ability to interpret bacterial GWAS results on a dataset of 1556 N. meningitidis strains 6 . Unlike the original study, we ran an analysis pooling the discovery and the replication data sets.…”
Section: Neisseria Data Setmentioning
confidence: 99%
“…The second dataset we used to test panfeed consists of 1,556 N. meningitidis strains, for which phenotypic data on the induction of invasive meningococcal disease (IMD) in their hosts was measured 6 . Earle et al found a SNP in the 5' untranslated region of fHbp (fHbp-7T) that was significantly associated with IMD-positive strains in a discovery and replication dataset consisting of a total of 1,556 strains.…”
Section: Simpler Pangenome Fine Mapping Of Associated Variantsmentioning
confidence: 99%
See 1 more Smart Citation